Influence of Fibrinogen Degradation Products (FDP) on Platelet Aggregation, Adhesiveness and Viscous Metamorphosis - Kowalski, E; Kopeć, M; Wegrzynowicz, Z (Thrombosis and Haemostasis, 1963)
Influence of SKPL on platelet function tests has been studied.1. Human platelets suspended in borate buffer lose after SKPL treatment the ability to aggregate under the influence of thrombin, ADP and connective tissue extract.2. Washed platelets incubated with SKPL did not influence the thrombin time of prothrombin free plasma.3. The digestion of platelet rich plasma with SKPL diminished the ability of platelets to aggregate under the influence of thrombin, ADP and connective tissue extract and the adhesiveness to glass.4. Viscous metamorphosis after addition of thrombin or ADP was delayed and less advanced in SKPL treated platelet rich plasma as compared with control undigested plasma.5. The addition of FDP preparation to platelet suspension or to platelet rich plasma impaired their ability to aggregate under the influence of thrombin, ADP and connective tissue extract.6. Adhesiveness of platelets to glass in the whole blood containing FDP was decreased in comparison with controls.7. FDP inhibits also the adhesion of platelets from platelet rich plasma to connective tissue fibers (collagen).8. Viscous metamorphosis induced by thrombin, ADP or connective tissue extract in platelet rich plasma could be delayed or inhibited by addition of FDP.9. Inhibiting effect of FDP on platelet functions were dependent on concentration of FDP and aggregating agent. FDP influence platelet functions in such concentration which inhibit significantly the thrombin time. Increase of the concentration of the inducing agent can overcome the inhibitory effects of FDP.10. The significance of the described findings for the hemostatic function of platelets is discussed.